The Impact of Instant Coffee and Decaffeinated Coffee on the Gut Microbiota and Depression-Like Behaviors of Sleep-Deprived Rats - Gu, Xinyi; Zhang, Shuyi; Ma, Weini; Wang, Qixue; Li, Ying; Xia, Chenyi; Xu, Ying; Zhang, Ting; Yang, Li; Zhou, Mingmei (Frontiers in Microbiology, 2022)
Objective Based on our previous research, chronic paradoxical sleep deprivation (PSD) can cause depression-like behaviors and microbial changes in gut microbiota. Coffee, as the world’s most popular drink for the lack of sleep, is beneficial to health and attention and can eliminate the cognitive sequelae caused by poor sleep. The purpose of this study is to investigate the effects of coffee and decaffeinated coffee on PSD rats. Research Design and Methods A total of 32 rats were divided into four groups: control group, PSD model group, conventional coffee group, and decaffeinated coffee group. Behavioral tests, including sucrose preference test, open field test, forced swimming test, and tail suspension test, as well as biochemical detection for inflammatory and antioxidant indexes were performed. The effects of coffee and decaffeinated coffee on the gut microbiota of PSD rats were investigated by 16S rRNA gene sequencing. Results Coffee and decaffeinated coffee significantly improved the depression-like behaviors. Moreover, the serum levels of interleukin-6 and tumor necrosis factor alpha were decreased in both coffee and decaffeinated coffee groups, as well as the levels of superoxide dismutase and GSH-Px were increased. Gut microbiota analysis revealed that the abundance of S24-7, Lachnospiraceae, Oscillospira, and Parabacteroides were significantly increased in PSD rats, while the abundance of Akkermansia and Klebsiella were significantly decreased. After the treatment of coffee and decaffeinated coffee, the abundance of the above gut microbiota was all restored in different degrees. Coffee had relatively more significant effects on PSD-induced depressive-like behaviors, while the difference between coffee and decaffeinated coffee was not obvious in correcting the disorder of gut microbiota. Conclusions These findings have shown that both coffee and decaffeinated coffee are effective for sleep deprivation-induced depression-like behaviors and the dysbiosis of gut microbiota and indicated that caffeine may be not the only key substance of coffee for regulating gut microbiota.